Community transmission of hepatitis B virus in Egypt: results from a case–control study in Greater Cairo - Jimenez, Adela Paez; El-Din, Noha Sharaf; El-Hoseiny, Mostafa; El-Daly, Mai; Abdel-Hamid, Mohamed; El Aidi, Saeed; Sultan, Yehia; El-Sayed, Nasr; Mohamed, Mostafa Kamal; Fontanet, Arnaud (International journal of epidemiology, 2009)
Background To identify current risk factors for hepatitis B virus (HBV) transmission in Greater Cairo. Methods A 1:1 matched case–control study was conducted in two ‘fever’ hospitals in Cairo. Acute hepatitis B cases were patients with acute hepatitis, positive HBs antigen, and high anti-HBc IgM titres. Control subjects were acute hepatitis A patients (positive anti-HAV IgM) or relatives of patients diagnosed with acute hepatitis C, identified at the same hospitals, with no past HBV infection (negative anti-HBc) and matched to cases on the same age and sex. Conditional logistic regression was used to identify factors associated with acute hepatitis B. Results Between April 2002 and June 2006, 233 cases and 233 controls were recruited to the study. In multivariate analysis, factors associated with an increased HBV risk in males were illiteracy [odds ratio (OR) = 6.1, 95% confidence interval (CI) = 2.8–13.1], shaving at barbers (OR = 2.1, 95% CI = 1.1–3.9) and injecting drug use (IDU) (OR = 3.4, 95% CI = 1.0–11.4). In females, factors associated with an increased HBV risk were illiteracy (OR = 2.2, 95% CI = 1.0–5.0), recent (<1 year) marriage (OR = 42.0, 95% CI = 3.8–463.9 compared with single women) and giving birth (OR = 3.7, 95% CI = 1.0–13.9). Conclusion In this study, HBV transmission took place primarily in the community, whether as a result of recent marriage (presumably first sexual intercourse), shaving at barbershops or IDU, and was more common among illiterates. Health promotion campaigns should be carried out to increase awareness about community transmission of HBV. In addition to routine immunization for infants and other populations, premarital screening might be useful to identify at-risk spouses in order to propose targeted immunization.